Fracture of Ceramic Liner and Head in a Total Hip Arthroplasty with a Sandwich Type Cup - Diego Reátegui; Sebastián García; Guillem Bori; Xavier Gallart (Case Reports in Orthopedics)
Due to its advantages, ceramic-on-ceramic bearings have been widely used in young patients for almost 30 years. Long-term survivorship, low wear, and low biological reactivity to particles are some of its characteristics. Even though this material has had a lot of improvements, the risk of fracture is one of the concerns. There have been reports of fracture of ceramic in the acetabular liner and head but no fractures of both in the same patient. We report a case of a fracture in a sandwich type acetabular liner and the ceramic head in a patient involving ankylosing spondylitis. It occurred three years after the operation and with no history of direct trauma. We decided to change the bearing surfaces to metal polyethylene without removing the metal back. The patient is satisfied by the clinical results after a 5-year followup.